Seafloor expression and shallow structure of a fold-and-thrust system, Isfjorden, west Spitsbergen - Maria Blinova; Jan Inge Faleide; Roy H. Gabrielsen; Rolf Mjelde (Polar Research, 2012)
A detailed map of the structure of the west Spitsbergen fold-and-thrust belt in the Isfjorden area, Spitsbergen, is presented. The map was constructed from a dense grid of two-dimensional multichannel reflection seismic and bathymetric data. Joint interpretation of two data sets allowed a comparison of tectonic structures detected along the uppermost parts of the seismic sections and those reflected in the morphology of the seafloor. Three major, predominantly north-west–south-east striking faults were identified. The westernmost fault (T1) is a hinterland-directed (most likely out of sequence) thrust, while the central and easternmost faults (T2 and T3) are foreland-directed (in-sequence thrusts). The thrusts divide Isfjorden into three subareas. Subarea 1 is bounded by thrust faults T1 and T2 and comprises Tertiary rocks surrounded by Jurassic–Cretaceous strata. The structural signature of Subarea 1 is that of a system of hinterland- and foreland-directed thrust faults, resulting in a seafloor relief characterized by parallel ridges and troughs. Subarea 2 is limited by thrust faults T2 and T3 and shows Jurassic–Cretaceous outcrops on the seafloor. Subarea 3 is situated east of the main thrust fault T3 and mainly involves outcrops of Triassic–Jurassic rocks. Together, Subareas 2 and 3 are dominated by foreland-directed, north-west–south-east and NNW–SSE-striking thrusts that are hardly detectable in bathymetric data.